Effect of foam sclerotherapy on healing and long-term recurrence in chronic venous leg ulcers. - Kulkarni, SR; Slim, F; Emerson, L; Davies, C; Bulbulia, R; Whyman, MR; Poskitt, K (2013)
INTRODUCTION: The ESCHAR trial showed that superficial venous surgery and compression in chronic venous ulceration achieved a 24-week healing rate of 65% and 12-month recurrence rate of 12%. Foam sclerotherapy treatment is an alternative to surgery. The aim of this study is to assess the effect of foam sclerotherapy on ulcer healing and recurrence in chronic venous leg ulcers. METHODS: Chronic venous leg ulcers (CEAP [clinical, aetiological, anatomical and pathological elements] 5 and CEAP 6) with superficial venous reflux were treated between March 2006 and June 2011 with ultrasound-guided foam sclerotherapy and compression.Venous duplex was performed on all legs before and after treatment. Twenty-four-week ulcer healing and one- and four-year ulcer recurrence rates were calculated using Kaplan–Meier survival analysis. RESULTS: Two hundred legs (186 patients) with chronic venous ulcers (CEAP 5: n ¼ 163 and CEAP 6: n ¼ 37) were treated with foam sclerotherapy. Complete occlusion was achieved in 185/200 (92.5%) limbs, short segment occlusion in 14/200 (7%) limbs and one leg segment failed to occlude. One patient suffered an asymptomatic non-occlusive deep vein thrombosis (DVT) diagnosed on duplex scan at one week and one presented with an occlusive DVT three weeks following a normal scan at one week. One patient developed an asymptomatic occlusive DVT at two weeks following a non-occlusive DVT diagnosed on initial one-week scan. Eighteen patients were lost to follow-up (3 moved away and 15 died of unrelated causes). The 24-week healing rate was 71.1% and one- and four-year recurrence rates were 4.7% and 28.1%, respectively. CONCLUSION: Foam sclerotherapy is effective in abolition of superficial venous reflux and may contribute to similar ulcer healing and long-term recurrence rates to superficial venous surgery. Foam sclerotherapy is an attractive alternative to surgery in this group of patients.